Focus of the first government announcements on COVID-19 in the Evaprop countries. - Carretón-Ballester, Carmen; Fernández Souto, Ana Belén; Almansa-Martínez, Ana María (Pontificia Universidad Católica de Chile, 2024)
The communication of those responsible for managing the COVID-19 crisis was largely improvised and constantly changing, especially in the initial phase. This article analyzes the global and comparative communication approach during the first official statements of the governments of the Evaprop Network countries (Argentina, Brazil, Chile, Colombia, Costa Rica, Spain, Mexico and Panama), following two key moments of the World Health Organization communication in the evolution of the health crisis. To this end, we applied content analysis to the public relations techniques used: press releases about the new coronavirus (first milestone, January 2020) and press conferences about COVID-19 after it was declared a global pandemic (second milestone, March 2020). The results provide an overview of the topics covered and the approach taken overall and by each country at both milestones. In addition to the different thematic interest and approach at the two points in time, the biggest differences can be found in the messages announced at the press conferences of the main leaders.
Enfoque de las primeras comunicaciones gubernamentales sobre COVID-19 en países de Evaprop
Keywords: Comunicación en las organizaciones; COVID-19 - En los medios de comunicación social; COVID-19; Government communication; Press conference; Press release; Crisis communication